Electroless Bimetal Decoration on N‐Doped Carbon Nanotubes and Graphene for Oxygen Reduction Reaction Catalysts. (27th March 2014) - Lee, Won Jun; Choi, Dong Sung; Lee, Sun Hwa; Lim, Joonwon; Kim, Ji Eun; Li, Dong Jun; Lee, Gil Yong; Kim, Sang Ouk
<x xml:space="preserve">Abstract</x> N‐doped sites at carbon nanotubes and graphene trigger the spontaneous decoration of bimetal (Pt and Pd) particles by the facile electroless redox reaction. The created hybrid catalyst yields remarkable current density (≈2.44 mA cm−2), lower onset potential (≈0.13 V), higher electron transfer number ≈4), and long‐term stability for oxidation–reduction reactions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>